Embodied Neoliberalism: Epidemiology and the Lived Experience of Consumer Debt. (July 2018) - Sweet, Elizabeth; DuBois, L. Zachary; Stanley, Flavia
A growing set of epidemiological data links personal financial debt to negative mental and physical health outcomes. These findings point to debt as a potentially significant socioeconomic determinant of population health, especially given rising rates of household and consumer debt in industrialized nations. However, the political and economic contexts in which rising consumer debt is embedded and the ways in which it is experienced in everyday life are underexplored in this epidemiological literature. This gap leaves open questions about how best to situate and understand debt as a health determinant with both psychosocial and neo-material attributes. In this article, we discuss findings from a qualitative study of personal debt experience in Boston, Massachusetts. Participants' debt narratives highlight the powerful feelings of shame, guilt, and personal responsibility that debt engenders. The findings point to the influence of neoliberal ideology in shaping emotional responses to debt and suggest that these responses may be important pathways through which debt affects health. We discuss our findings within the broader landscape of American neoliberal economic policy and its role in shaping trends of consumer debt burden.